Tolerance and Pharmacokinetics of Recombinant Human Endostatin Administered as Single-Dose or Multiple-Dose Infusions in Patients With Advanced Solid Tumors: A Phase I Clinical Trial. (December 2021) - Wang, Xu; Shi, Yehui; Jia, Yongsheng; Zhao, Weipeng; Zhang, Li; Bai, Guiying; Ren, Yulin; Chen, Yong-Zi; Tong, Zhongsheng
Objective : This study aimed to investigate the tolerance and pharmacokinetic characteristics of recombinant human endostatin (rh-endostatin) administered as single-dose or multiple-dose infusions in patients with advanced solid tumors.Methods : This phase I trial was designed as a single-center, single-arm, nonrandomized, open-label, dose-escalation study. The trial consisted of 2 parts: a single-dose part and a multiple-dose part, each with 3 dose comparison groups. Rh-endostatin was administered as an intravenous injection only once at a dose of 5 mg/m 2, 7.5 mg/m 2, or 10 mg/m 2 in the single-dose part and as a daily intravenous injection for 14 days at the same doses in the multiple-dose part. The serum pharmacokinetics, toxicity and immunogenicity of rh-endostatin were evaluated.Results : Dose-limiting toxicity (DLT) was not observed in any group. A few patients developed cardiotoxicity, such as QT prolongation or narrow arrhythmia. Other adverse events were slight coagulation abnormalities and haematological abnormalities. For rh-endostatin doses of 5 mg/m 2, 7.5 mg/m 2, and 10 mg/m 2, the mean Cmax values in the single-dose part were 344 ± 38.7 ng/mL, 524 ± 157 ng/mL, and 800 ± 201 ng/mL, respectively, and the average AUC0−t values were 3290 ± 3790 ngh/mL, 4940 ± 4380 ngh/mL, and 5050 ± 3980 ngh/mL, respectively. The Cmax ss values of the 3 doses in the multiple-dose part were 575 ± 270 ng/mL, 531 ± 106 ng/mL, and 864 ± 166 ng/mL, respectively, and the AUC0−τ values were 3610 ± 1040 ngh/mL, 3290 ± 1090 ngh/mL, and 5180 ± 1210 ngh/mL, respectively. The Cmax of a single-dose regimen showed linear kinetic characteristics. The patients in the single-dose group were negative for serum antibodies against rh-endostatin, while one patient in the multiple-dose group was positive.Conclusions : Rh-endostatin as a daily intravenous injection for 14 days in patients with advanced solid tumors is safe and well tolerated, without DLT, at doses of 5 mg/m 2, 7.5 mg/m 2, and 10 mg/m 2 . Serum antibodies against rh-endostatin were very low after multiple infusions. For phase II trials, the recommended rh-endostatin dose is 10 mg/m 2 as a daily intravenous injection for 14 days.